A critical account of what "geography" means to primary trainee teachers in England. Issue 2 (3rd April 2018) - Puttick, Steven; Paramore, John; Gee, Nick
ABSTRACT: Research on trainee teachers' conceptions of geography has criticised their views for being limited, and failing to appreciate the breadth or depth of geography. A body of research in this area has developed over the past two decades, producing well-established classifications through which to analyse conceptions of geography. This contribution breaks from these classifications by offering a critical review of the existing literature and then, drawing on critical theory, distinguishing between geography as knowing, understanding, and acting. Findings from a survey of first year undergraduate primary trainee teachers ( n = 42) are analysed through this critical framework, and it is argued that there is a distinct Cartesian duality in the way that respondents see the world as an object of study for learners as cognising subjects. This is argued to be problematic and, in response, a moral vision for school geography is outlined that represents geography in terms of a critical praxis.